2012
DOI: 10.3363/prb.27.18
|View full text |Cite
|
Sign up to set email alerts
|

STUDY OF SOME PARAMETERS TO OBTAIN THE P<SUB>2</SUB>O<SUB>5</SUB> WATER- SOLUBLE FROM PARTIALLY ACIDULATED PHOSPHATE ROCKS (PAPRs) BY SULFURIC ACID

Abstract: The work presented in this paper deals with the determination of optimum parameters during the partial acidulation of the phosphate ore of Djebel Onk (Algeria) and the determination of P 2 O 5 water-soluble. The first part is devoted to P 2 O 5 conversion rate during partial acidulation of phosphate with different particle sizes (80 μm, 160 μm and 250 μm). These conversion rates are obtained by performing a series of reactions between phosphate and sulfuric acid diluted from 10 to 50 wt% and with reaction time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…However, most of these have not been utilized because of their low solubility and reactivity (13). Methods for increasing the solubility of PR by partial acidulation and calcination have been reported previously (14)(15)(16)(17). The International Fertilizer Development Center has promoted partial acidulation with sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these have not been utilized because of their low solubility and reactivity (13). Methods for increasing the solubility of PR by partial acidulation and calcination have been reported previously (14)(15)(16)(17). The International Fertilizer Development Center has promoted partial acidulation with sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…The International Fertilizer Development Center has promoted partial acidulation with sulfuric acid. Acidulation of PR produces the phosphate component monocalcium phosphate, small amounts of dicalcium phosphate, and residual apatite depending on the degree of acidulation (16). However, the viscosity and acidity of the product increase with increasing amounts of sulfuric acid because of the unbound sulfuric acid (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Increased dissolution of the rock phosphates when added to soils may also be attributed to the neutralization of the OHions, released on hydrolysis of the phosphate ions, due to soil acidity. (Chhonkar, 1994, Mizane, andRehamnia, 2012)) also reported that P availability to plants was significantly increased in soil.…”
Section: Resultsmentioning
confidence: 91%
“…After drying for 8 days, only on the surface of blanks containing 90 wt% sand, "down" appears. It consists of evaporation products of water soluble salts, which are present in clay and sand (see Table II) [36]. A characteristic feature of these blanks is the bad cohesion of sand particles due to the small content of montmorillonite in the composition.…”
Section: Preparation Of Blanksmentioning
confidence: 99%